Competition law compliance programmes: An interdisciplinary approach - Paha, Johannes (Springer International Publishing, 2016)
This book reviews and presents antitrust law compliance programmes from different angles. These programmes have been increasingly implemented and refined by firms over recent years, and various aspects of this topic have been researched. The contributions in this book extend beyond the treatment of legal issues and show how lawyers, economists, psychologists, and business scholars can help design antitrust law compliance programmes more effectively and run them more efficiently.
CRIS-Team Scopus Importer:2022-11-17